Hybrid cascade control for a class of nonlinear dynamical systems. (April 2019) - Campos-Rodríguez, A.; García-Sandoval, J.P.; González-Álvarez, V.; González-Álvarez, A.
Highlights: A hybrid cascade control scheme with continuous and discrete measurements is proposed. The inner loop uses on-line continuous measurements to regulate a key variable. The outer loop updates the inner loop reference at each sampling period. The scheme has a reset observer to update the state vector at intersampling periods. Abstract: The regulation of nonlinear dynamical systems with both continuous and discrete measurements is addressed by a robust control structure that considers the compromise between safety, productivity and quality. This structure is a hybrid cascade control scheme composed of an inner loop which uses on-line or fast enough measurements to regulate a key variable and updates its reference at each sampling period according to the available discrete information of the outer loop. The cascade control scheme includes a reset observer to update the state vector at the intersampling periods, enhancing the robustness of the closed-loop in the face of parametric uncertainty and load changes. A bifurcation study was also carried out to determine the state and control bounds that guarantee the operation of the nonlinear system under safe and attainable conditions, making the saturation limits an instrumental part of the cascade control design to guarantee closed loop stability for systems with multiple stable and/or unstable open loop equilibrium. The performance of the proposed cascade control scheme is illustrated via numerical simulations in two extreme study cases: an open loop unstable chemical reactor and a highly sensitive bioprocesses used in high yield wastewater treatment.